2021
DOI: 10.4269/ajtmh.21-0391
|View full text |Cite
|
Sign up to set email alerts
|

Residence Time, Water Contact, and Age-driven Schistosoma mansoni Infection in Hotspot Communities in Uganda

Abstract: Schistosomiasis is the second most important parasitic infection after malaria in terms of its socioeconomic impact and is endemic in 78 countries. It affects more than 240 million people worldwide, with 90% of cases occurring in sub-Saharan Africa. In Uganda, Schistosoma mansoni is the most common species, with more than seven million people infected and 17 million living at risk despite mass drug administration (MDA) of praziquantel initiated more than 16 years ago. There has been a shift in the WHO schistos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…However, high intensities are also strongly associated with high levels of water contact activities [ 29 , 61 , 62 ]. Corroborating quantitative research in Bugoto [ 50 ] that showed people contacting lake water daily and for long hours, we observed people engaging daily with high-risk water contact activities, regardless of age and gender, reinforcing the notion that schistosomiasis is hard to prevent. We observed and heard that people continue with their daily activities at, and in, the lake whether they are aware of the risk or not, because it is the major source of livelihood and free water.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, high intensities are also strongly associated with high levels of water contact activities [ 29 , 61 , 62 ]. Corroborating quantitative research in Bugoto [ 50 ] that showed people contacting lake water daily and for long hours, we observed people engaging daily with high-risk water contact activities, regardless of age and gender, reinforcing the notion that schistosomiasis is hard to prevent. We observed and heard that people continue with their daily activities at, and in, the lake whether they are aware of the risk or not, because it is the major source of livelihood and free water.…”
Section: Discussionsupporting
confidence: 78%
“…mansoni : Bugoto, Bwondha, and Musubi, all on the shores of Lake Victoria in Mayuge District, Eastern Uganda ( Fig 1 ). In these communities prevalence and intensities are high, for example 71% of people are infected in Bugoto community, [ 50 ] with likely similar infection levels in Musubi and Bwondha [ 27 , 37 ]. Infection risk behaviour is also high [ 50 ], whilst MDA coverage remains low [ 15 , 50 ] despite over 15 years of annual MDA indicating that additional, locally informed, improved interventions are needed.…”
Section: Methodsmentioning
confidence: 99%
“…It is plausible that relatively low levels of water contact are sufficient for becoming infected. A study by Moses et al [ 63 ] in Uganda noted that water contact duration of as little as five minutes per day was significantly associated with S . mansoni infection risk.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that relatively low levels of water contact are sufficient for becoming infected. A study by Moses et al [63] in Uganda noted that water contact duration of as little as five minutes per day was significantly associated with S. mansoni infection risk. Therefore, water contact intensity may be less relevant for predicting individual-level infection status than knowledge on whether someone had any water contact [46].…”
Section: Water Contact Frequency and Durationmentioning
confidence: 99%
“…The disease compromises public health by contributing to malnutrition in children, preventing them from attending school, impairing cognitive development, and increasing high risk of getting HIV especially in women [2,7,15,16]. Although given present effective interventions, SCH remains the second to malaria in terms of its public health signi cance [8, 17,18]. Professional and domestic activities such as farming, bathing, washing, and playing expose local dwellers to infection [19][20][21][22].…”
mentioning
confidence: 99%